2020
DOI: 10.1038/s41598-020-74720-7
|View full text |Cite
|
Sign up to set email alerts
|

Marital status and survival of patients with colorectal signet ring cell carcinoma: a population-based study

Abstract: The prognostic role of marital status on colorectal signet ring cell carcinoma (SRCC) has not been studied. In this study, the correlation of marital status with prognosis of colorectal SRCC was analyzed. Eligible subjects were extracted from the Surveillance, Epidemiology, and End Results (SEER) dataset from 2004 to 2015, followed by comparison of cancer-specific survival (CSS) and overall survival (OS) between married and unmarried group. 3152 patients were identified including 1777 married patients (56.38%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
(38 reference statements)
0
11
1
Order By: Relevance
“…It is known that marital status can impact psychological conditions and the general health of individuals. Married patients have fewer emotional consequences such as distress and depression compared to other patients when they are diagnosed with cancer as their partners may share part of the emotional burden 21 , 22 . Compared to unmarried patients, the beneficial effects of marriage on health are associated with a higher quality of life, greater financial resources and wider social support 23 .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that marital status can impact psychological conditions and the general health of individuals. Married patients have fewer emotional consequences such as distress and depression compared to other patients when they are diagnosed with cancer as their partners may share part of the emotional burden 21 , 22 . Compared to unmarried patients, the beneficial effects of marriage on health are associated with a higher quality of life, greater financial resources and wider social support 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported on small samples of CDC cases and investigated the their clinico-pathological characteristics and prognosis (6,7). However, these studies did not have a large sample size and did not include some non-clinical factors, such as race, marital status and economic status, which have been shown to be risk factors in other researches (8)(9)(10). In addition, there is no model to predict the prognosis of CDC, and an accurate prediction model is important for patient follow-up and treatment decisions (11).…”
Section: Introductionmentioning
confidence: 99%
“…It is reasonable that spouse and family support plays a positive role in antitumor treatment and tumor surveillance [26]. Feng et al have also revealed the similar findings [27], who suggest that the distress and psychological burden following tumor diagnosis could be shared and relieved by spouse support [28,29]. Further stratified analyses of marital status and LTSs suggest that marital status is significantly associated with LTSs in 3).…”
Section: Discussionmentioning
confidence: 73%